Knowledge and awareness on usage of mouth masks among dental fraternity during this pandemic COVID-19: A cross-sectional study - Ravichandra Ravi; Srividya Athkuri; Charishma Chowdary Ponugubati; Roopesh Borugadda; Sahithi Pamidimukkala; Abdul Afraaz (Asian Journal of Medical Sciences, 2020)
Background: The pandemic caused by novel coronavirus (SARS-CoV-2) in Wuhan, China, in December 2019 is a highly infectious disease. The World Health Organization (WHO) has declared the outbreak of Corona Virus Diseases (COVID 19) as a global public health emergency. Currently, research on novel coronaviruses is still in the primary stage.